The Wajo Police Strategy in Addressing and Preventing the Misuse of Traditional Badik Weapons among the Bugis Community in Wajo Regency - Setiyawan, Theodorus Echeal; Setiono, Joko; Koto, Zulkarnaen (Greenation Publisher & Yayasan Global Resarch National, 2025)
The misuse of traditional badik knives in Wajo Regency is a complex phenomenon rooted in the badik's status as a cultural symbol of the Bugis people. Although the badik has historical value and cultural significance, social reality shows that this weapon is often misused in various criminal acts such as assault, fighting, and murder. This phenomenon poses a unique challenge for law enforcement agencies, particularly the Wajo Police Department, in maintaining public order without offending deeply rooted cultural values. This study aims to examine the strategies employed by the Wajo Police Department in addressing and preventing the misuse of the badik through a legal approach that synergizes with local social and cultural aspects. The research method used is normative juridical with a legislative approach and literature study. The results of the study show that the Wajo Police Department applies three main approaches, namely preventive, repressive, and restorative. The preventive approach is carried out through legal socialization and strengthening the role of Bhabinkamtibmas based on Perpol No. 1 of 2021 concerning Community Policing. The repressive approach is based on the provisions of Emergency Law No. 12 of 1951 and the Criminal Code. Meanwhile, the restorative approach refers to Police Regulation No. 8 of 2021, involving traditional leaders and community leaders. An evaluation of the strategy indicates the need for local regulations (Perda) that more strictly regulate the use of badik, as well as enhance the capacity of law enforcement officers in a culture-based approach. The synergy between national law and local wisdom is key to addressing the issue of traditional weapon misuse without erasing the cultural identity of the community.